First steps towards the online diagnostic assessment of foreign language vocabulary (Pedagógiai Értékelési Konferencia, 2013)
The symposium presents initial results from a research project on English and German foreign language vocabulary of 6th graders. The aims of the project were (1) to explore the methods of diagnostic assessment of foreign language vocabulary, (2) to develop diagnostic tests for the assessment of word knowledge, (3) to compare the size and characteristics of students’ English and German vocabulary, and (4) to test the possibilities of online assessment of foreign language vocabulary. It is widely accepted that the level of foreign language vocabulary influences the general language proficiency, mostly at the beginning of language learning (Schoonen and Verhallen, 2008). Being at the beginning of foreign language learning, 6th grade students have to use de‐contextualized word knowledge, and they are expected to know vocabulary passively. In this research, passive recognition of the words (Laufer et al., 2004) was the focus of the assessment. The research aimed at creating and testing a measurement tool of word knowledge with visual stimuli. Picture association is a widely used method in the acquisition of new words and it can also be used in the assessment of students’ word knowledge (De Groot and Van Hell, 2005). Pictures are also applied in the assessment of vocabulary of young children (Dunn and Dunn, 1997). For the assessment of English and German foreign language vocabulary, two online diagnostic test triplets were developed. They covered the same basic vocabulary outlined in the national curriculum, and they were identical in their structure. Tests were administered using the eDIA online diagnostic assessment system that stored both item responses and task‐solving times. Differences between English and German vocabulary were analyzed on overall test performances, on task levels and in terms of the levels of the Common European Framework of Reference for Languages (CEFR) (2001). Presentations of the symposium will (1) give a concise literature review on the assessment of foreign language vocabulary, (2) highlight the sources and the methodology of selecting the words for the tests, (3) report on the test results, on the similarities and differences between the results of the English and German test versions, and (4) analyze the results and experiences of online diagnostic testing of foreign language vocabulary. The comparative assessment of two foreign language vocabularies of students is not usual in foreign language research. The use of visual stimulus and assessing young learners make our instrument probably unique in this field. The online testing of foreign language vocabulary can be regarded as a new and effective assessment method. This assessment procedure provides both the student and the teacher with immediate feedback on the vocabulary acquired.